2022
DOI: 10.3390/pathogens12010063
|View full text |Cite
|
Sign up to set email alerts
|

Association and Effectiveness of PAX1 Methylation and HPV Viral Load for the Detection of Cervical High-Grade Squamous Intraepithelial Lesion

Abstract: Background: PAX1 methylation (PAX1m) and HPV viral load (VL) have been reported to detect cervical high-grade squamous intraepithelial lesions (HSIL), but the relationship between them is unclear. This study aimed to evaluate the correlation between HPV VL and PAX1m and its effectiveness in predicting cervical lesions. (2) Methods: A total of 476 women referred to colposcopy for abnormal cervical screening at the Peking University People’s Hospital between November 2020 and November 2021 were enrolled. PAX1m a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Although some studies [19,38] have explored the correlation between HPV VL and disease severity, other findings proposed that HPV VL levels did not show any significant association with type-specific hrHPV persistence or subsequent development of cervical intraepithelial neoplasia, especially within women under 30 with normal cytology [39]. It seems that HPV16/18 VL plays a crucial role in contributing to HPV persistency [40] and was positively correlated with the grade of cervical lesions (CIN3 > CIN2 > CIN1, p < 0.05) [30]. However, it has also been found that lower HPV VL and viral genome integration predict the persistence of HPV16 but not the progression of a persistent HPV16 infection to CIN3+ in women with normal cytology [41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some studies [19,38] have explored the correlation between HPV VL and disease severity, other findings proposed that HPV VL levels did not show any significant association with type-specific hrHPV persistence or subsequent development of cervical intraepithelial neoplasia, especially within women under 30 with normal cytology [39]. It seems that HPV16/18 VL plays a crucial role in contributing to HPV persistency [40] and was positively correlated with the grade of cervical lesions (CIN3 > CIN2 > CIN1, p < 0.05) [30]. However, it has also been found that lower HPV VL and viral genome integration predict the persistence of HPV16 but not the progression of a persistent HPV16 infection to CIN3+ in women with normal cytology [41].…”
Section: Discussionmentioning
confidence: 99%
“…Normalization of HPV type-specific VLs was executed using the formula: VL = log10[(CnHPV/CnTOP3) × 10,000] copies/10,000 cells, where CnHPV represents the quantity of HPV DNA and CnTOP3 denotes the number of human cells. The experimental protocol closely followed the procedures outlined in previous reports [30,34].…”
Section: Methylation and Hpv Viral Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, studies have demonstrated that the PAX1m level can accurately distinguish between high‐grade cervical intraepithelial neoplasia (CIN) lesions and CC, particularly in CC screening or triage testing of mildly abnormal cytology. Moreover, PAX1m has been indicated to reduce the referral rate to colposcopy via triage of high‐grade squamous intraepithelial lesions 9 and contributes to predicting the pathological upgrade of CIN before cold knife conization 10 . Recent studies have also shown that PAX1m levels may predict the efficacy of chemoradiotherapy in CC patients 11 .…”
Section: Introductionmentioning
confidence: 99%